(untitled) (Olhares, 2025)
The field of Dramatic Writing, a genre that cannot do without ontological elements such as conflict, for example, is the target of constant attacks by authors who follow the dominant precepts of their own historical contexts. This paper, supported by the ideas of Raymond Williams and Jean-Pierre Sarrazac, problematizes the defense of the supremacy of the epic in drama, in the work of Peter Szondi and the concept of post-dramatic, in the book of the same name by Hans-Thies Lehmann, bringing them together , respectively, from the teleological thought of the 19th century and the liquid thought of postmodernity, questioning the pertinence and relevance of these ideas in relation to the multifaceted dramatic literary genre.